Frugal Innovations: Implementation in Regions of Poland - Jacek Woźniak (European Management Studies)
Purpose: The objective of the study is to assess the complexity of applying the attributes of frugal innovations in innovative enterprises located in three regions of Poland (i.e. A, B and C), as well as to compare the three regions. Design/Methodology/Approach: The study included 200 large innovative enterprises. The study listed the following number of enterprises belonging to individual regions: A – 154 entities, B – 39 entities, as well as C – 7 entities. Six hypotheses have been stated in the study. The empirical study considered quantitative methods and research techniques, i.e. the Computer Assisted Web Interview (CAWI) survey technique, and statistical analysis of quantitative data. The basic research tools were: the CAWI survey questionnaire, PS IMAGO PRO 7.0 software and Microsoft Excel. Findings: The study indicated that: (1) in the A and B regions – both in the area of shaping relationships with customers and shaping innovative processes –moderately high values of Indicator of the Complexity of Shaping Relationships with Customers (ICSRC) and Indicator of the Complexity of Shaping Innovative Processes (ICSIP) indicators were recorded, as well as in the C region, the values are moderately low for both indicators, (2) in the A region, there is a higher level of the complexity of applying the attributes of the concept of frugal innovations with respect to shaping relationships with customers and shaping innovative processes than in the B and C regions. Implications/limitations: In Poland, there are rather favorable conditions for the implementation of the attributes of the concept of frugal innovations – this is indicated by relatively small differences between the A and B regions. Therefore, in theoretically less developed voivodeships from the so-called Polish B region, frugal innovations are implemented. The research conducted indicates that greater emphasis should be placed on spreading knowledge about frugal innovations in the C Region, which can draw on the experience and support of the A region. Originality/value: The study raises a new issue in domestic science, concerning the implementation of the attributes of the concept of frugal innovations in various regions of Poland, i.e. the A, B and C regions.